IMPLEMENTASI PROGRAM INDONESIA PINTAR PADA JENJANG PENDIDIKAN SEKOLAH MENENGAH PERTAMA DI SMP 3 SATU ATAP GEBOG KUDUS - Illiya Arina Riska; Dewi Rostyaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Indonesia Pintar Program, hereinafter referred to as PIP, is a government cash aid granted to learners whose parents are not and / or less able to finance their education, as a continuation and expansion of the target of the Bantuan Siswa Miskin program (BSM). The method used in this research is descriptive qualitative method. The purpose of this research is to see how the implementation of Indonesia Pintar Program (PIP) in SMP Negeri 3 Satu Atap Gebog Kudus and to analyze factors influencing its implementation by using Van Meter and Van Horn implementation theory. The problems of implementation of the Indonesia Pintar Program are among others, the purpose and objectives, socialization, data collection mechanism and verification, fund distribution, communication, resources, characteristics of implementing agents and social environment. The recommendation given is that the implementing agency should be more responsible for coordinating the junior high schools and the channeling banks, be able to pay attention to the human resources involved in this Smart Indonesia program to be more adequate not only the quantity but also the quality, the implementing agent must be able to be firm and strict the violations that occur, for the social environment, especially the parents of the Smart Indonesia Program beneficiaries, should be better understood and comply with the provisions and technical program of Indonesia Pintar.